(untitled) (Medical Forum Monthly, 2022)
Objective: To compare the outcome of manual vacuum aspiration and evacuation of retained products of conception in 1st trimester miscarriages. Study Design: Randomized Controlled Trial study. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Bahawal Victoria Hospital, Bahawalpur from March 2019 to September 2019. Materials and Methods: A total of 216 patients between the age of 18-40 were included in the study with 1st trimester miscarriages. Patients with signs of septic abortion, ectopic pregnancy, CRF, CLD and any bleeding disorders were excluded. Group A patients underwent evacuation manually by manual vacuum aspiration (MVA) while group B patients underwent evacuation of retained products of pregnancy (ERPC). Outcome variables like blood loss, hospital stay, perforation and incomplete evacuation were noted. Results: The mean age of women in group A was 29.59 ± 4.76 years and in group B was 28.08 ± 5.83 years. Gestational age was from <12 weeks with mean gestational age of 7.83 ± 2.41 weeks. In this study, mean blood loss was seen in MVA as 58.70 ± 13.26 ml and 73.99 ± 9.96 ml in ERPC with p-value of 0.0001. Also hospital stay was seen in MVA as 30.94 ± 4.65 hours and 46.26 ± 4.76 hours in ERPC with p-value of 0.0001. Incomplete evacuation was found in ERPC group as 00 (0.0%) and in MVA group as 02 (1.85%) with p-value of 0.155. The uterine perforation was seen in 12 (11.11%) patients of ERPC group and 4 (3.70%) patients of MVA group with p-value of 0.038. Conclusion: Conclusion of the study was that manual vacuum aspiration (MVA) is a safe procedure for first trimester miscarriages as compared to evacuation of retained products of conception.